Heat transfer hysteresis under liquid binary mixtures boiling - V. V. Kozhokaru; E. V. Lykov; E. S. Zhelonkina (Advanced Engineering Research, 2018)
Introduction. Heating dynamics under binary mixtures pool boiling is considered. The work objective is to experimentally investigate the hysteresis on heat flux under the liquid binary mixtures boiling. Materials and Methods. The experiments were conducted on a cylindrical heater which served as a resistance thermometer and a generated power. The heating was carried out by a quasisteady-state method. Binary liquid mixtures were the target of the research. Research Results. The experiments result in obtaining boiling curves under the saturated and unsaturated boiling. On the generated heating and cooling curves, several specific areas are observed. The first is the area where heat exchange is carried out in a liquid through convection, and the second is the bubble boiling region where the hysteresis is detected by the heat flux. The liquid flashing is followed by the noise generation and a jump in the mean temperature of the heating surface. The hysteresis of heat transfer is found out on the curve α (Тст). The heating curve always passes below the cooling curve. That is, for the given heater temperature, the heat-transfer factor will always be greater under cooling than under heating. This fact is observed both under single and multiple heating and cooling. The boiling curve is two dependences q (Тст) and α (Тст) synchronously obtained in one experiment. The hysteresis of the heat-transfer coefficient is detected on the boiling curve under heating and cooling of the heater. Discussion and Conclusions. Along with the hysteresis on the heat flux of the boiling mixtures, the hysteresis of the heattransfer coefficient is first detected. The cause of hysteresis on the heat flux is various heat-transfer values on the heating and cooling curves at any specified Тст. The heating dynamics shows that the heating curve, both for heat fluxes and for the heat-transfer factor, always passes at lower values of these quantities (q и α) than the cooling curve.